A Mixed Comparisons of Different Intensities and Types of Physical Exercise in Patients With Diseases Related to Oxidative Stress: A Systematic Review and Network Meta-Analysis - Lu, Zhenghui; Xu, Yining; Song, Yang; Bíró, István; Gu, Yaodong (Frontiers in Physiology, 2021)
The balance of oxidation and antioxidation systems has a significant meaning for the human body. As one of the approaches that could improve body health, physical exercise seems to regulate this balance. Besides, intaking antioxidant supplements is also a common choice to enhance the balance of oxidation and antioxidation systems. To understand the effects of these two interventions on oxidative and antioxidant systems in adults with oxidative stress-related diseases, the network meta-analysis was used to compare the mixed effects of high-intensity training (HIT), medium-intensity training (MIT), low-intensity training (LIT), and antioxidant supplements. This systematic review includes all eligible randomized controlled trials in PubMed, Medline, Cochrane Library, and CINAHL. Twelve of the studies met the inclusion criteria (n=766 participants at study completion). The results show that in the long-term study, malondialdehyde (MDA) was better treated by HIT, and superoxide dismutase (SOD) was better treated by LIT. In acute studies, MIT combined with antioxidant supplements can better improve MDA and SOD. Comprehensive consideration of MDA and SOD, long-term MIT combined with antioxidant supplements may effectively improve oxidative stress in non-healthy populations. However, more research is needed on the effect of antioxidant supplements on oxidative stress in unhealthy people.